CULTIVATING A SENSE OF PATRIOTISM IN RUSSIAN LANGUAGE LESSONS IN FOREIGN LANGUAGE GROUPS OF HIGHER EDUCATIONAL INSTITUTIONS - Aripjanova Sh. G. (Bright Mind Publishing, 2025)
The article examines the development of a sense of patriotism in Russian language lessons in foreign language groups of higher education institutions.
Keywords: Patriotism, foreign language students, education.